Lichen amyloidosis treated with topical combination therapy and narrowband ultraviolet B phototherapy - Hasibah, Ulfah Hasna; Ferina, Siti Aisha Nabila; Komarasari, Eka; Esti, Prima Kartika; Angin, Lenti Perangin (UI Scholars Hub, 2023)
Background: Lichen amyloidosis (LA) is characterized by linear rows of firm, pigmented, grouped, hyperkeratotic papules that can form a plaque, usually occurring on the shins and forearms, with intense itch as the prominent symptom. Case Illustration: A 57-year-old female complained of brown spots on her shins and arms that gradually thickened six years ago. The lesions were brown, multiple, discrete, slightly scaly papules forming hyperpigmented plaques. The result of the histopathology examination showed an acanthotic epidermis with hyperkeratotic foci and eosinophilic amorphous mass deposits in the papillary dermis with brown pigments. The working diagnosis was lichen amyloidosis. Topical treatments were ointment consisting of 6% salicylic acid mixed with clobetasol propionate ointment 0.05% used once daily and emollient used twice daily. Narrowband ultraviolet B (NB-UVB) was administered at a dose of 300 mJ/cm2 once a week and increased by 10-20% on the next episodes. After six weeks of treatment, there were no new brown spots, the lesions became thinner and less erythematous, and the itch decreased significantly. Discussion: The factors that induce and worsen LA are pruritus and scratching. Topical combination therapy of salicylic acid and corticosteroid can increase the effectiveness of treatment on thick, scaly plaque lesions. NB-UVB was found to reduce pruritus. Conclusion: Topical combination therapy of keratolytic agents and potent corticosteroids can be used as a non-invasive therapy to improve skin lesions by thinning these lesions in LA patients. NB-UVB phototherapy has also been significantly shown to relieve a patient’s severe itch.